Analisis Efisiensi Biaya Persediaan Bahan Baku dan Biaya Produksi dengan Metode JIT pada PT An-Flex Perkasa Kota Batam - Oktaviani, Oktaviani; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2021)
The purpose of this research is to acknowledge (1) the application of just in time method for PT An-Flex Perkasa, (2) the obstacles happened during the implementation of JIT method in PT An-Flex Perkasa industry, and (3) efficiency of raw material supply costs, production costs by using Just In Time (JIT) system at PT An-Flex Perkasa. This study was descriptive with quantitative approachment. The result of the study showed that (1) the application of the Just In Time method at PT An-Flex Perkasa is carried out by producing based on orders from customers, so that raw material purchases are made when needed to produce hydraulic hose, (2) The obstacle in applying the Just In Time method is that the company incurs a higher cost of ordering raw materials, (3) just in time method period 2015-2019 PT An-Flex Perkasa was more efficient to be used in applying raw materials cost with an efficiency amount of 0,00030% it means non efficient and while JIT method period 2015-2019 PT An-Flex Perkasa was more efficient to be used in applying production cost with an efficiency amount of 1,69% it means very efficient.